Performance of concrete beams strengthened with FRP rods: A review - Jasim, Basma W.; Al-Azzawi, Adel A. (Al-Salam Journal for Engineering and Technology, 2024)
Ductility is a critical property in structural engineering, ensuring that beams can undergo significant deformation before failure, thereby giving plenty of notice before disastrous collapse. This study investigates the ductility properties of constructions that have been reinforced using FRP rods, which are increasingly popular due to their corrosion resistance, superior strength with low mass, and durability. Traditional steel reinforcement has well-documented ductility properties, but FRP bars, due to their brittle nature, pose challenges in achieving the desired ductility levels in structural applications. This research evaluates various factors influencing FRP-reinforced beams' ductility, including the type of FRP material, the hybridization of FRP with other reinforcing materials, and the effect of utilizing fibres in the mixtures to enhance the mechanical characterstics of concrete. Studies have indicated that the ductility of beams can be enhanced using hybrid rebar systems, which integrate steel and fibre reinforced polymer. However, complex and expensive production methods limit their practical application. Using steel bars with FRP bars can significantly incresese seriviceability requiremts such as crack width and deflection, but they also lower corrosion resistance, especially in aggressive environments. The beams' overall ductile behavior is primarily determined by the concrete's characteristics. Fibres greatly increase the mechanical characteristics, toughness, and ductility of the concrete mix, strengthening the bond between bars and the concrete and improving the overall performance of the beam.